Air and gas drilling manual : applications for oil, gas, geothermal fluid recovery wells, specialized construction boreholes, and the history and advent of the directional DTH.: applications for oil, gas, geothermal fluid recovery wells, specialized construction boreholes, and the history and advent of the directional DTH. (2020) - Lyons, William C; Stanley, James H; Sinisterra, Francisco J; Weller, Tom
No abstract available